2019
DOI: 10.1371/journal.pone.0212298
|View full text |Cite
|
Sign up to set email alerts
|

Integrating genetic and physical positions of the anthracnose resistance genes described in bean chromosomes Pv01 and Pv04

Abstract: A complex landscape of anthracnose resistance genes ( Co- ) located at the telomeric regions of the bean chromosomes Pv01 and Pv04 has been reported. The aim of this work was to investigate the genetic and physical positions of genes conferring resistance to races 6, 38, 39, 357, 65, and 73 as well as the relationships among the resistance genes identified herein and the previously described Co- genes in these telomeric regions. The linkage analysis using a genetic map of 497 SNPs from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…The common bean genome also contains NBS-LRR regions that are distributed across all chromosomes ( Ferrier-Cana et al, 2003 ; Richard et al, 2017 ; Wu et al, 2017 ) and a recent GWAS study showed associations between these NBS-LRR regions with anthracnose resistance ( Wu et al, 2017 ). Anthracnose resistance genes Co-3 and its alleles, Co-16 are mapped to common bean Pv04 and this study also found association of SNPs on Pv04 with anthracnose resistance to races 3, 87, and 503 ( Geffroy et al, 1999 ; David et al, 2008 ; Coimbra-Gonçalves et al, 2016 ; Murube et al, 2019 ). The Co-3 4 locus was previously mapped on the 3.36-Mb genomic position but it was recently mapped to the region between 0.49 to 0.58 Mb on Pv04 ( Valentini et al, 2017 ) which indicates shift in the physical positions with better mapping tools ( Kelly and Bornowski, 2018 ).…”
Section: Discussionsupporting
confidence: 67%
“…The common bean genome also contains NBS-LRR regions that are distributed across all chromosomes ( Ferrier-Cana et al, 2003 ; Richard et al, 2017 ; Wu et al, 2017 ) and a recent GWAS study showed associations between these NBS-LRR regions with anthracnose resistance ( Wu et al, 2017 ). Anthracnose resistance genes Co-3 and its alleles, Co-16 are mapped to common bean Pv04 and this study also found association of SNPs on Pv04 with anthracnose resistance to races 3, 87, and 503 ( Geffroy et al, 1999 ; David et al, 2008 ; Coimbra-Gonçalves et al, 2016 ; Murube et al, 2019 ). The Co-3 4 locus was previously mapped on the 3.36-Mb genomic position but it was recently mapped to the region between 0.49 to 0.58 Mb on Pv04 ( Valentini et al, 2017 ) which indicates shift in the physical positions with better mapping tools ( Kelly and Bornowski, 2018 ).…”
Section: Discussionsupporting
confidence: 67%
“…In addition to these genes, the borders contain genes encoding LRR. The second region contains 13 annotated genes, one of which encodes a protein kinase and another which encodes a protein related to the biotic stress response (Murube et al., 2019). In the interval region considered to build an integrated map, we observed the presence of 29 NBS‐LRRs and four kinases (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…To identify sources of resistance against the ANT pathogen, a panel of 14 Andean cultivars were screened for their reactions to ten Mesoamerican (9,64,65,73,89,445,453,1545,2047, and 3481) and six Andean (2,7,19,23,39, and 55) races of C. lindemuthianum ( Table 1). The genomic locations of the known Co genes in each cultivar, except for Jalo Vermelho, Jalo Pintado 2, and CDRK (Table 1), have been previously reported [25,28,29,30,31,32,53]. We observed that five genotypes known to carry alleles at the Co-1 locus (MDRK, Kaboon, Perry Marrow, AND 277, and Widusa) showed different spectra of ANT resistance (Table 1), supporting the hypothesis that they indeed carry different alleles of Co-1 or additional unidentified Co loci.…”
Section: Resultsmentioning
confidence: 81%
“…The candidate region containing the CoPv01 CDRK and PhgPv01 CDRK loci in linkage group Pv01 is located close to one of the most important clusters of ANT resistance genes in the common bean genome [32]. The Pv01 cluster includes the following ANT disease-resistance genes: Co-1, Co-1 HY , Co-1 4 ; Co-x, Co-Pa, Co-AC, and Co-1 X [23,25,28,29,30,31,53,68]. The CoPv01 CDRK /PhgPv01 CDRK loci was found in a genomic region flanked by the markers ss715645251 (50,301,532 bp) and ss715645248 (50,546,925 bp) on Pv01 (Fig 1).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation